Does p‐lactate increase in patients with GSD1 after ingesting a meal with common‐size sources of fructose and galactose? Observations from a prospective, non‐blinded, crossover pilot study - Camilla Diana B. Caroee; Allan M. Lund (JIMD Reports)
Abstract Ingestion of fructose and galactose may result in elevated lactate concentrations in patients with glycogen storage disease type 1 (GSD1). In this randomized cross‐over pilot study, 7 patients with GSD 1a (6) and GSD1b (1) orally consumed a common‐size fructose and galactose from either 200 mL of skimmed milk, 200 mL juice or 200 mL water. This was given after a night with their usual dietary treatment using either cornstarch, glycosade or continuous feed. P‐lactate and ‐glucose were measured 2 h before dosing (T = −120 min and −60 min). At baseline (T = 0), p‐lactate, p‐glucose, p‐triglycerides, p‐uric acid and p‐alanine were measured just before dosing. P‐lactate and p‐glucose were measured every 30 min for 4 h. Four hours after the consumption (T = 240 min, end‐of‐test), levels of p‐lactate, p‐glucose, p‐triglycerides, p‐uric acid and p‐alanine were measured. P‐lactate increased in three patients with mean of 0.3 mmol/L (range 0.2–0.6 mmol/L) after consuming milk. The highest level was seen after 60 min. A decrease was seen in three patients. P‐lactate increased in four patients with a mean increase at 1.3 mmol/L (range 0.2–2.2 mmol/L) after consuming 200 mL juice. A peak increase was seen after the first 30 min in two patients whereas the peak in the remaining two patients was at 60 min; all values decreased to baseline values after further 60 min. In two patients, p‐lactate was unchanged, respectively, decreased after juice ingestion. Calculation of galactose and fructose AUC percentage change after challenge did not reveal consistent increase or decreases.